EFFECT OF TOP MANAGEMENT TEAM BEHAVIORAL INTEGRATION IN PROMOTION ORGANIZATIONAL AMBIDEXTERITY: ANALYTICAL RESEARCH AT THE UNIVERSITY OF BAGHDAD - Tariq Kadhim Shlaka; Prof. Dr. Ahmed Karim Jassem (Scholar Express Journals, 2022)
The current research aims to test the effect of the TMT behavioral integration on Organizational Ambidexterity at the University of Baghdad, as well as diagnosing the level of interest of the researched faculties in the research variables. , As for the research sample, it was a stratified intentional, which included (204) represented by (deans, assistant deans, heads of departments), and the main research tool (the questionnaire) was distributed to them to survey opinions about the variables investigated, while the research used statistical programs (AMOS V.23-SPSS V. 23) to analyze the primary data, with the adoption of descriptive and inferential statistics methods, to test the research hypotheses. organizational). The research concluded with a set of recommendations, including “the need to increase the interest of the senior administrations of the colleges under study in developing the necessary plans to explore and invest the environmental opportunity and to provide sufficient time and requirements for the analysis and interpretation of data and information obtained from their internal and external environment. And to build bridges of trust and cooperation between senior leaders and subordinates in order to contribute to their contribution.” In building an effective organization.
Keywords: management; behavioral; Organizational; University